2002
DOI: 10.1046/j.1528-1157.2002.28501.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Status Epilepticus with Pentobarbital, Propofol, or Midazolam: A Systematic Review

Abstract: Summary:Background: New continuous infusion antiepileptic drugs (cIV-AEDs) offer alternatives to pentobarbital for the treatment of refractory status epilepticus (RSE). However, no prospective randomized studies have evaluated the treatment of RSE. This systematic review compares the efficacy of midazolam (MDL), propofol (PRO), and pentobarbital (PTB) for terminating seizures and improving outcome in RSE patients.Methods: We performed a literature search of studies describing the use of MDL, PRO, or PTB for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
411
4
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(448 citation statements)
references
References 56 publications
11
411
4
22
Order By: Relevance
“…The reported incidence of refractory SE is 9 to 38%, and mortality in that group is generally higher than in other SE patients, from 16 to 100% 24 . The incidence (36.2%) and mortality rate (57.9%) of refractory SE in our sample were similar to those in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…The reported incidence of refractory SE is 9 to 38%, and mortality in that group is generally higher than in other SE patients, from 16 to 100% 24 . The incidence (36.2%) and mortality rate (57.9%) of refractory SE in our sample were similar to those in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…EEG may also be used to gauge success at achieving electrographic suppression or burst suppression, which has been associated with decreased likelihood of relapsed status epilepticus following barbiturate therapy [95] with fewer breakthrough seizures [96].…”
Section: Gauging the Response To Treatmentmentioning
confidence: 99%
“…The studies conducted on the termination of seizures in NCSE patients at the emergency department are limited, whereas the medications used for standard SE patients are known to have benefits (10). In a review by Maganti et al (8) on NCSE, they reported that IV benzodiazepines could be given as first-line therapy followed by IV phenytoin, phenobarbital, or valproic acid.…”
Section: Discussionmentioning
confidence: 99%